Nomenclatural novelties in Baccharis subgen. Baccharis (Asteraceae, Astereae) - Heiden, Gustavo (Phytotaxa, 2020)
Four new names (Baccharis gaucha for B. axillaris var. dentata; B. neoaustralis for B. papillosa subsp. australis; B. neotruncata for B. truncata, and B. tetroica for B. tricuneata var. procumbens) and 12 new combinations at species rank (B. chaparensis, B. chrysophylla, B. fimbriata, B. integrifolia, B. kessleri, B. longipedicellata, B. minor, B. mornicola, B. pycnocephala, B. vargasii, B. viscosissima, and B. yungensis) are provided totalling 16 nomenclatural novelties for Baccharis subgen. Baccharis. Moreover, a neotype is designated for B. mornicola. Comments on the distribution of these species and their closest congeneric species are provided, as well as morphological characters to differentiate them.